Teachers' Subjective Construction in Natural and Social Science Subjects - Yoga Dhamantara; Agus Suprijono; Neni Mariana (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
The implementation of the integration of the Natural Sciences and Social Sciences (IPAS) curriculum in elementary schools is one of the significant changes in the Indonesian education curriculum, which is expected to improve the quality of education and prepare students to face future challenges. However, the implementation of IPAS also faces a number of obstacles and challenges that need to be overcome. This research aims to identify the main obstacles faced by schools in implementing IPAS. The research will use a mixed methods approach combining qualitative and quantitative methods. The data we collect will be analyzed using statistical software and qualitative analysis techniques to identify key patterns and findings. The results of this research will provide valuable insights that can support efforts to improve basic education in Indonesia, and bridge the gap between learning policies and practices in elementary schools. In future research, it is hoped that it can sharpen the discussion of science and science learning in elementary schools which not only discusses the material but also approaches to learning.